Effect of strain-rate on flexural behavior of composite sandwich panel - Abdi, Behzad (2012)
In the past few decades, Composite Sandwich Panel (CSP) technology significantly influenced the design and manufacturing of high performance structures. Although using CSP increases the reliability of structure, the important concern is to understand the complex deformation and damage evolution process. This study is focused on the mechanical behaviour of CSP under flexural loading condition. A setup of three-point bending test is prepared using three support span of 40, 60 and 80 mm. The loading was controlled by three different displacement rates of 1, 10 and 100 mm per minute to examine the effects of strain-rate on bending behaviour of CSP material. The beam span significantly affects the flexural stiffness of CSP panel. The load-deflection response of the panel shows two different portions, that representing equivalent elastic and plastic regions in both the core and facesheets components of CSP. The non-combustible mineral-filled core appears to be nonlinear in the elastic region, at high loading rate. Consequently the failure occurs as the core/facesheets interface suffers debonding.